The double‐edged effect of knowledge acquisition: How contracts safeguard pre‐existing resources - Zanarone, Giorgio; Lo, Desmond (Ho‐Fu); Madsen, Tammy L. (Strategic Management Journal, 2016)
Research summary : Acquiring knowledge on a partner's pre‐existing resources plays an important yet ambiguous role in collaborative relationships. We formally model how contracts trade off productive and destructive uses of knowledge in a buyer‐supplier relationship. We show that, when the buyer's pre‐existing resources are vulnerable to the revelation of sensitive knowledge, the supplier overinvests in knowledge acquisition as it expects to use the knowledge as a threat in price negotiations. A non‐renegotiable closed‐price contract prevents such overinvestment and reduces the supplier's ability to expropriate the buyer ex post. Our results extend to the cases of renegotiable closed‐price contracts, repeated interactions between a buyer and a supplier, and the use of nondisclosure policies. We draw theoretical, empirical, and managerial implications from our model . Managerial summary : This study yields new insights regarding the use of contract design in protecting pre‐existing, nonrelationship specific assets in buyer‐supplier arrangements. Anecdotal examples illustrate the “dark side” of these arrangements where opportunistic suppliers exploit knowledge of buyers' pre‐existing resources to seek rent and appropriate value. When a supplier is likely to act harmfully, a closed‐price contract that specifies the price of the supplier's component upfront may reduce the supplier's incentives to overinvest in acquiring and exploiting knowledge of the buyer's pre‐existing resources. As such, when a buyer's pre‐existing resources are highly valuable, and thus more vulnerable to use by the supplier outside of the arrangement, a non‐renegotiable closed‐price contract is more efficient. Additionally, limited disclosure policies and informal agreements based on repeated interactions complement indirect governance via price contracts . Copyright © 2015 John Wiley & Sons, Ltd.